Development of teaching materials on algebra using the mind mapping model with a scientific approach - Nada, Yohanes Hariaman (Universitas Islam Sultan Agung, 2023)
Most students dislike studying mathematics because they believe it contains much difficult material. Algebra is one of the topics considered difficult to learn in mathematics. The teaching material used is one factor that influences the low mastery of material in algebraic language. This research aims to develop valid teaching material using the Mind Mapping mode for algebraic topics. The modules and leaflets of the students' activities are the materials made. This research refers to the Kemp model, which consists of 10 stages of development. However, the scope of this research is only from the need analysis stage to the validation stage. Device validation sheets are used as data collection tools. This research uses qualitative and quantitative data analysis methods. Three people - a lecturer, a teacher, and a ninth-grade student - validate the teaching material that has been made. The results of the validation stage show that the teaching material is declared valid with little revision. The results of this study show that the teaching material is ready to be implemented.